Muscle strength and pulmonary function in individuals with chronic kidney disease: a cross-sectional study: Muscle strength and pulmonary function in chronic kidney disease - Rocha, Lívia Gomes da; Policarpo, Júlio Henrique; Cunha, Beatriz Luiza Marinho; Silva, Juliana Rodrigues da; Marinho, Patrícia Érika de Melo (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Respiratory muscle weakness in chronic kidney disease (CKD) is described by decline in lung function and respiratory pressures in patients who are still in the conservative stage of the treatment. Objective: To assess respiratory muscle strength and lung function in patients in stages 4 and 5 of CKD. Methods: It was a cross-sectional study developed between February and July 2015 at an university hospital, and approved by the Institutional Ethics Committee (Report No. 1.360.173). Patients of both sexes, aged between 18 and 59 years, and diagnosed with CKD stages 4 and 5 non-dialytic were included. There were collected information about gender, age, comorbidities, and length of treatment for kidney disease. Inspiratory and expiratory muscle strength (manovacuometry) and lung function [forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, and peak expiratory flow (PEF) (portable digital spirometer)] were assessed. Results: 22 patients in the CKD stages 4 and 5 participated of this study, they presented a prevalence of inspiratory muscle weakness of 70% and 75% and expiratory muscle weakness 90% and 83.3%, respectively. In terms of lung function, patients in the CKD stage 4 had lower spirometrics values. Conclusion: Patients in the stages 4 and 5 of CKD undergoing by the conservative treatment had reduced respiratory muscle strength and changes in the pulmonary function.